Oral health planning in João Pessoa municipality , Paraíba State: Dental surgeons as protagonists of Basic Care - doi 10.4025/actascihealthsci.v34i2.10576 - Yuri Wanderley Cavalcanti; Ronaldo Lira Júnior; Laryza Neves Delmondes; Rosana Leal do Prado; Wilton Wilney Nascimento Padilha (Universidade Estadual de Maringá, 2012)
The aim was to identify the perception of Oral Health Planning (OHP) of basic care (BC) dental surgeons (DSs) in João Pessoa, Paraíba State, Brazil. Seventeen BC DSs from João Pessoa were interviewed. A qualitative analysis was performed using the Discourse of the Collective Subject (DCS) methodology. DCS obtained: Impact - "My work is effective when the user's need remains at the BC". Social Control - "The population participates in the organization of promotional activities, but I think it doesn't have enough maturity to opine on OHP". OHP Basis and Organization - "The OHP has a diverse organization and is based on user needs". It can be concluded that the knowledge of the DSs on OHP is varied. There is limited understanding about problem-solving. Social control is considered incipient and weak. It is understood that the organization of the local OHP assumes a diverse character and should be based on user demands.